Overcoming Obstacles to Education: The Experience of Women University Students Diagnosed with Attention-Deficit / Hyperactivity Disorder - Dwyer, Sonya Corbin (Canadian Journal of Higher Education, 2000)
Much of the research on Attention-Deficit / Hyperactivity Disorder (AD/HD) has been conducted with male children, resulting in limited knowledge of the disorder in females and adults. Even though increasing numbers of students with the disorder are entering postsecondary institutions, AD/HD in this population is an understudied area. A hermeneutic phenomenological methodology was chosen to explore the experience of eight women university students diagnosed with AD/HD. Two themes describing obstacles to their education, Robbed of Time and Thoughts Like a Rubber Ball, were identified. Strategies and treatment issues, implications for educators and mental health professionals, and directions for future research are considered.